Bone and the Immune System. (October 2017) - Weitzmann, M. Neale
Osteoporosis increases fracture risk, a cause of crippling morbidity and mortality. The immunoskeletal interface (ISI) is a centralization of cell and cytokine effectors shared between skeletal and immune systems. Consequently, the immune system mediates powerful effects on bone turnover. Physiologically, B cells secrete osteoprotegerin (OPG), a potent anti-osteoclastogenic factor that preserves bone mass. However, activated T cells and B cells secrete pro-osteoclastogenic factors including receptor activator of Nuclear factor-kappaB (NF-kB) ligand (RANKL), Interleukin (IL)-17A, and tumor necrosis factor (TNF)-α promoting bone loss in inflammatory states such as rheumatoid arthritis. Recently, ISI disruption has been linked to osteoporosis in human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome (AIDS), where elevated B cell RANKL and diminished OPG drive bone resorption. HIV-antiretroviral therapy paradoxically intensifies bone loss during disease reversal, as immune reconstitution produces osteoclastogenic cytokines. Interestingly, in estrogen deficiency, activated T cells secrete RANKL, TNF, and IL-17A that amplify bone resorption and contribute to postmenopausal osteoporosis. T cell–produced TNF and IL-17A further contribute to bone loss in hyperparathyroidism, while T cell production of the anabolic Wingless integration site (Wnt) ligand, Wnt10b, promotes bone formation in response to anabolic parathyroid hormone and the immunomodulatory costimulation inhibitor cytotoxic T lymphocyte–associated protein-4-IgG (abatacept). These findings provide a window into the workings of the ISI and suggest novel targets for future therapeutic interventions to reduce fracture risk.